PERBANDINGAN METODE GEOGRAPHICALLY WEIGHTED PRINCIPAL COMPONENT ANALYSIS REGRESSION (GWPCAR) DAN GEOGRAPHICALLY WEIGHTED RIDGE REGRESSION (GWRR) - Santoso, Esti Herdina; Soehono, Loekito Adi; Sumarminingsih, Eni (Jurnal Mahasiswa Statistik, 2014)
'